The Roles of Organic Acids in C4 Photosynthesis - Ludwig, Martha (Frontiers in Plant Science, 2016)
Organic acids are involved in numerous metabolic pathways in all plants. The finding that some plants, known as C4 plants, have four-carbon dicarboxylic acids as the first product of carbon fixation showed these organic acids play essential roles as photosynthetic intermediates. Oxaloacetate, malate, and aspartate are substrates for the C4 acid cycle that underpins the CO2 concentrating mechanism of C4 photosynthesis. In this cycle, oxaloacetate is the immediate, short-lived, product of the initial CO2 fixation step in C4 leaf mesophyll cells. The malate and aspartate, resulting from the rapid conversion of oxaloacetate, are the organic acids delivered to the sites of carbon reduction in the bundle-sheath cells of the leaf, where they are decarboxylated, with the released CO2 used to make carbohydrates. The three-carbon organic acids resulting from the decarboxylation reactions are returned to the mesophyll cells where they are used to regenerate the CO2 acceptor pool. NADP-malic enzyme-type, NAD-malic enzyme-type and phosphoenolpyruvate carboxykinase-type C4 plants were identified, based on the most abundant decarboxylating enzyme in the leaf tissue. The genes encoding these C4 pathway-associated decarboxylases were co-opted from ancestral C3 plant genes during the evolution of C4 photosynthesis. Malate was recognized as the major organic acid transferred in NADP-malic enzyme-type C4 species, while aspartate fills this role in NAD-malic enzyme-type and phosphoenolpyruvate carboxykinase-type plants. However, accumulating evidence indicates that many C4 plants use a combination of organic acids and decarboxylases during CO2 fixation, and the C4-type categories are not rigid. The ability to transfer multiple organic acid species and utilize different decarboxylases has been suggested to give C4 plants advantages in changing and stressful environments, as well as during development, by facilitating the balance of energy between the two cell types involved in the C4 pathway of CO2 assimilation. The results of recent empirical and modeling studies support this suggestion and indicate that a combination of transferred organic acids and decarboxylases is beneficial to C4 plants in different light environments.